Towards Frameworking a Strategic Approach for Festival Tourism Destination Marketing and Management: Case study of Odisha, (India) - Mohanty, Patitapaban (Turizam, 2018)
The integral part of human travel from ancient age has been the result of interlinking of religion and tourism. Religious tourism, the tourism which is motivated by the belief and faith has been proved from the millennia. The symbolic and hectic nature of modern tourism has become sought after touristic activities due to the numerous religious festivals which are very often termed as a sacred sojourn. That is how festival tourism has been considered as one of the prominent part of religious tourism, more concentrated with spiritualism, divinity, blending with and driving towards culture, tradition, and heritage. Festival tourism is now viewed as an alternative to the religious tourism for cultural and heritage resurgence, renaissance and awakening, transcending the border of religiosity into universal humanity and spirituality. This paper attempts to throws some lights on destination management and marketing from the context of festival tourism. Hence the purpose of this paper is to identify the roles and responsibilities of DMMO in order to develop a suitable strategic approach framework for festival tourism.